2014 European Guideline on HIV testing - Gökengin, Deniz; Geretti, Anna Maria; Begovac, Josip; Palfreeman, Adrian; Stevanovic, Milena; Tarasenko, Olga; Radcliffe, Keith (SAGE Publications, 2014)
Testing for HIV is one of the cornerstones in the fight against HIV spread. The 2014 European Guideline on HIV Testing provides advice on testing for HIV infection in individuals aged 16 years and older who present to sexually transmitted infection, genito-urinary or dermato-venereology clinics across Europe. It may also be applied in other clinical settings where HIV testing is required, particularly in primary care settings. The aim of the guideline is to provide practical guidance to clinicians and laboratories that within these settings undertake HIV testing, and to indicate standards for best practice.